2005
DOI: 10.1016/j.rapm.2005.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subtenon Anesthesia Combined With General Anesthesia on Perioperative Analgesic Requirements in Pediatric Strabismus Surgery

Abstract: We conclude that preoperative subtenon bupivacaine 0.5% compared with a saline injection contributed to reduction of perioperative pain and undesirable side effects in pediatric strabismus surgery performed under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…The results showed a significantly lower occurrence of OCR and postoperative pain in the bupivacaine treated group. [7] This study was repeated by Tuzcu et al in 2014 and they found no significant difference in the occurrence of OCR between normal saline and bupivacaine injected groups. [8] Contrary to Tuzcu et al and in agreement with Steib et al, our results clearly demonstrated that compared to the normal saline group who received the same anesthetic regimen and underwent a similar procedure performed by the same surgeon, the sub-Tenon bupivacaine injected group had a significantly lower incidence of OCR.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The results showed a significantly lower occurrence of OCR and postoperative pain in the bupivacaine treated group. [7] This study was repeated by Tuzcu et al in 2014 and they found no significant difference in the occurrence of OCR between normal saline and bupivacaine injected groups. [8] Contrary to Tuzcu et al and in agreement with Steib et al, our results clearly demonstrated that compared to the normal saline group who received the same anesthetic regimen and underwent a similar procedure performed by the same surgeon, the sub-Tenon bupivacaine injected group had a significantly lower incidence of OCR.…”
Section: Discussionmentioning
confidence: 80%
“…[13] Steib et al reported that sub-Tenon's block with bupivacaine decreased postoperative pain when compared to a saline injected control group. [7] Tuzcu et al also reported that pain scores at 30 minutes after surgery and additional analgesic treatment needed during the postoperative period were significantly lower in the sub-Tenon bupivacaine group than in the control group. [8] Contrary to these studies, in the study performed by Ates et al, there was no significant difference in terms of postoperative analgesia in the retrobulbar block or subconjunctival local anesthetic infiltration groups compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations